Structural characterization of a novel cyclic 2,3-diphosphoglycerate synthetase involved in extremolyte production in the archaeon Methanothermus fervidus - De Rose, Simone A.; Isupov, Michail N.; Worthy, Harley L.; Stracke, Christina; Harmer, Nicholas J.; Siebers, Bettina; Littlechild, Jennifer A.; , The HotSolute consortium; Siebers, Bettina; Bräsen, Christopher; Stracke, Christina; Meyer, Benjamin; et al. (Frontiers in Microbiology, 2023)
The enzyme cyclic di-phosphoglycerate synthetase that is involved in the production of the osmolyte cyclic 2,3 -diphosphoglycerate has been studied both biochemically and structurally. Cyclic 2,3 -diphosphoglycerate is found exclusively in the hyperthermophilic archaeal methanogens, such as Methanothermus fervidus, Methanopyrus kandleri, and Methanothermobacter thermoautotrophicus. Its presence increases the thermostability of archaeal proteins and protects the DNA against oxidative damage caused by hydroxyl radicals. The cyclic 2,3-diphosphoglycerate synthetase enzyme has been crystallised and its structure solved to 1.7 Å resolution by experimental phasing. It has also been crystallised in complex with its substrate 2,3 diphosphoglycerate and the co-factor ADP and this structure has been solved to 2.2 Å resolution. The enzyme structure has two domains, the core domain shares some structural similarity with other NTP-dependent enzymes. A significant proportion of the structure, including a 127 amino acid N-terminal domain, has no structural similarity to other known enzyme structures. The structure of the complex shows a large conformational change that occurs in the enzyme during catalytic turnover. The reaction involves the transfer of the γ-phosphate group from ATP to the substrate 2,3 -diphosphoglycerate and the subsequent SN2 attack to form a phosphoanhydride. This results in the production of the unusual extremolyte cyclic 2,3diphosphoglycerate.